Dynamics - Lamb, Horace (Cambridge Cambridge university press, 1961)
Sir Horace Lamb (1849-1934) the British mathematician, wrote a number of influential works in classical physics. A pupil of Stokes and Clerk Maxwell, he taught for ten years as the first professor of mathematics at the University of Adelaide before returning to Britain to take up the post of professor of physics at the Victoria University of Manchester (where he had first studied mathematics at Owens College).
Keywords: Dynamics; Mathematics